2006
DOI: 10.1183/09031936.06.00114905
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1 and GSTP1 and respiratory health in asthmatic children exposed to ozone

Abstract: Acute exposure to ozone has been related to a wide spectrum of health effects in susceptible individuals. Genetic factors may influence interindividual variation in ozone response. The current authors investigated the relationships between common polymorphisms in two genes involved in response to oxidative stress, i.e. glutathione S-transferases M1 (GSTM1) and P1 (GSTP1), and both respiratory symptoms and lung function in response to ozone among childhood asthmatics.A total of 151 asthmatic children, who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
3
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 34 publications
(34 reference statements)
7
82
3
2
Order By: Relevance
“…We found that children with the GSTM1-null or the GSTP1 Val/Val genotype had greater increases in difficulty breathing in relation to ozone than other children (22). Increases were enhanced among children with both of these genotypes.…”
Section: Interaction Between Genetics and Ozone In Relation To Asthmamentioning
confidence: 57%
“…We found that children with the GSTM1-null or the GSTP1 Val/Val genotype had greater increases in difficulty breathing in relation to ozone than other children (22). Increases were enhanced among children with both of these genotypes.…”
Section: Interaction Between Genetics and Ozone In Relation To Asthmamentioning
confidence: 57%
“…Therefore, the GSTM1 null genotype would be expected to affect the individual's response to O 3 exposure, possibly causing increased susceptibility to oxidative injury. Since 2001, the results of several field studies showed that the GSTM1 null genotype is associated with greater acute lung function response and/or respiratory symptom response to O 3 -induced oxidative stress [21][22][23]. Other studies have suggested that the GSTM1 null genotype may play a significant role in the development of asthma in response to oxidative stress [24,25].…”
mentioning
confidence: 99%
“…GST genindeki polimorfizm, inflamasyona ve oksidatif strese karşı verilecek cevaba ve hava kirliliğinin ortaya çıkardığı olumsuz etkilerin artışına yol açabilir. Meksika'da yapılan bir çaışmada GST gen polimorfizmi olan astımlı çocuklarda ozon maruziyetinin daha fazla olduğu, bunun da dispnede ve nazal inflamasyonda artışa neden olduğu belirtilmiştir (38).…”
Section: Buket Mermit çIlingirunclassified